Pengaruh usia, jenis kelamin, tingkat pendidikan dan jumlah tanggungan Terhadap Pengembalian Kredit Pengusaha Kecil Pada Program Kemitraan PT Semen Baturaja (Persero) Tbk Bandar Lampung - Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2014)
This study was conducted to determine the factors that affect loan repayments the partners in the partnership program in 2010-2012. The population in this study are the partners who become trained partners in 2010-2012. Sampling study using purposive sampling method with several criteria: the partners who become trained partners in 2010-2012, the number of loans worth 50 million and 40 million, the partners complete data such as data age, gender, education level, number dependents, and the frequency of borrowing. The results of the study concludes that the gender variable and the number of dependents partially no effect on the repayment of credit, while the variable age and level of education is partially affect the loan repayment.